In women’s best interest: a case for mandatory reporting of gender-based violence on abused women’s behalf - Ramatsoma, Hlologelo Mphulo (Stellenbosch : Sellenbosch University, 2025)
Ramatsoma, Hlologelo. 2025. In women’s best interest: a case for mandatory reporting of gender-based violence on abused women’s behalf. Unpublished masters thesis. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/handle/10019.1/132475`